Analisis Determinan Yang Mempengaruhi Pengalokasian Belanja Modal Pada Kabupaten di Sumatera Utara - Ari Irawan; Debbi Chyntia Ovami; Nanda Fitrah Gemilang Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of regional original income, balancing funds, on the allocation of capital expenditures in districts/cities of North Sumatra province. This research method uses descriptive and quantitative data. The sample of this research is Regency/City APBD data in North Sumatra in 2018-2020. The results of the study indicate that the independent variables of Regional Original Revenue, Balancing Fund, Remaining Budget Financing simultaneously (together) affect the allocation of Capital Expenditures. Regency in North Sumatra Province. While the results of the coefficient of determination (R2) indicate that the analytical model used in this study is able to explain that all independent variables are Regional Original Income, Balancing Funds, Remaining Budget Financing (SilPA) on Capital Expenditure Allocation of Districts/Cities of North Sumatra Province, which is equal to 54%, and the remaining 46% is influenced by other factors outside of the regression model.